Theodahad : a platonic king at the collapse of Ostrogothic Italy - Vitiello, Massimiliano (University of Toronto Press, 2014)
Painting a picture of an unlikely king whose reign helped spell the end of Ostrogothic Italy, Vitiello's book not only illuminates Theodahad's own life but also offers new insight into the sixth-century Mediterranean world.